"Impossible" patients in oncology: Two unusual cases. Issue 1 (27th June 2018) - Reich, Michel; Tessier, Williams; Lemaire, Justine; Penel, Nicolas
Abstract: Objective: Cancer patients can present with impossible behavior, which can jeopardize their treatment and challenge healthcare professionals' teamwork. Method: Report of two unusual psychiatric cases, including Munchausen and Peter Pan syndromes, which occurred in a comprehensive cancer center. Result: Guidelines in medical and surgical wards are suggested to address such situations regarding oncologic compliance. Significance of results: Multidisciplinary collaboration between medical and surgical teams and the psycho-oncologic department is highly recommended.